What is the most effective medical treatment for nightmares in patients with PTSD?. Issue 8 (August 2015) - Leon, Enrique; Dawson, Gray N.
Abstract : Evidence‐based answer: Prazosin appears to decrease nightmare intensity and frequency in patients with posttraumatic stress disorder (PTSD) within 6 to 15 weeks (SOR: B, systematic review of RCTs, case series, retrospective chart reviews, and case reports). Many other medications, including clonidine, antipsychotics, cyproheptadine, antidepressants, and monoamine oxidase inhibitors, may also improve nightmares and insomnia in patients with PTSD (SOR: B, systematic review of open‐label, case‐report, and placebo‐controlled trials).